I spy with my little eye: a simple behavioral assay to test color sensitivity on digital displays - Alexander G. Knorr; Céline M. Gravot; Clayton Gordy; Stefan Glasauer; Hans Straka (Biology Open, 2018)
Passive and interactive virtual reality (VR) environments are becoming increasingly popular in the field of behavioral neuroscience. While the technique was originally developed for human observers, corresponding applications have been adopted for the research of visual-driven behavior and neural circuits in animals. RGB color reproduction using red, green and blue primary color pixels is generally calibrated for humans, questioning if the distinct parameters are also readily transferable to other species. In particular, a visual image in the RGB color space has a clearly defined contrast pattern for humans, but this may not necessarily be the case for other mammals or even non-mammalian species, thereby impairing any interpretation of color-related behavioral or neuronal results. Here, we present a simple method to estimate the sensitivity of animals to the three primary colors of digital display devices based on the performance of object motion-driven visuo-motor reflexes and demonstrate differences in the color sensitivity between Xenopus laevis and Ambystoma mexicanum (Axolotl). This article has an associated First Person interview with the first author of the paper.